Assessment of Selected Parameters of Sowing Quality of Vistula Parsley Seeds with a Precision Seed Drill with a Pneumatic Seeding System (Agricultural Engineering, 2020)
Results of laboratory tests on the sowing quality of Vistula parsley seeds with a working section of a seed drill by Weremczuk company Max Pneumatic S 156 model with a pneumatic sowing system were presented. Tests of the sowing section of a seed drill were carried out in laboratory conditions on a special stand. They showed that the seed drill speed and rotations of the sowing disc have a significant impact on the sowing quality expressed with participation of single, double sowing and passes. The most favourable results at all set distances between seeds in a row were obtained with a seed drill speed of 1 km·h−1. On the other hand, the increase of the working speed of a seed drill and rotations of a sowing disc influenced significantly the deterioration of the sowing quality.